PRINSIP-PRINSIP KEUANGAN PUBLIK ISLAM - Miftahul Huda Huda (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2018)
Islamic Public Finance is a financial concept based on Islam, which by planting religious values will have an impact on positive values. The source of Islamic public finances is certainly the largest base of acquisition is zakat, infak, sadakah, and waqf. The ultimate goal of Islamic public finance is the falah. Different characteristics of the conventional is a separate value of Islamic public finances, in which there are views on zakat and taxes, payments, expenses, and equilibrium in the public sector. The instruments that occur in public finance should also be considered, among others are zakat, corporate assets, infak, kharaj, waqf. The collected power of this public finance system has several foundations of Islamic values, which by these principles will make a firm foundation in developing Islamic public finances.